CYP21A2 genetic profile in 14 Egyptian children with suspected congenital adrenal hyperplasia: a diagnostic challenge. Issue 1 (21st December 2017) - Elmougy, Fatma; Sharaf, Sahar; Hafez, Mona; Khattab, Ahmed; Abou‐Yousef, Hazem; Elsharkawy, Marwa; Baz, Heba; Ekladious, Sherif; Sherif, Balsam; Musa, Noha; Elshiwy, Yasmin; Afif, Alaa; et al.
Abstract: CYP21A2 genotyping remains an important element in the diagnosis and management of congenital adrenal hyperplasia, and establishing accurate genotype–phenotype correlations has facillitated adequate genetic counseling and prenatal management for at‐risk families. Despite extensive efforts to establish a clear genotype–phenotype correlation, some discordance remains. Establishing a diagnosis of congenital adrenal hyperplasia on the basis of biochemical and clinical data is occasionally challenging, and the identification of CYP21A2 mutations may help confirm the diagnosis. We review the diagnostic challenges despite an extensive genetic evaluation for 14 patients with a suspected clinical and biochemical diagnosis of congenital adrenal hyperplasia. Other diagnostic entities should be considered in the absence of convincing genetic data.